RITUAL BABURU BABI DALAM FOTOGRAFI DOKUMENTER - putra, zebri winanda putra (Matalensa: Journal of Photography and Media, 2023)
The creation of a final project entitled "Baburu Pig Rituals in Documentary Photography" The object of this final project is to discuss the tradition of the Baburu Pig, which is a wild boar hunting activity carried out by a group of Minangkabau people, precisely in Patamuan District, Padang Pariaman Regency, West Sumatra. Baburu pigs are hunting activities to catch wild boars using dogs that have been trained to hunt. This activity can be found in every nagari in Minangkabau, and is usually followed by all people who like hunting. In the Babu Babi activity, male hunters from various regions in West Sumatra are involved. Baburu pig in the Patamuan District community is a ritual that is carried out in a gradual customary process. The pig hunting rite becomes a sign that involves various social aspects of the Patamuan District community, including customs and culture. This is the background for the creation of this final project because of the importance of maintaining a tradition or custom that has been passed down from generation to generation. To achieve this goal, observation, exploration and experimentation methods are needed. The observation method aims to dig deeper into the idea of creation by going directly into the field of creation objects. Next is the exploratory method, which is the process of building closeness to the object of creation. The next method is experimentation which aims to formulate techniques from the execution of photos to the creation of works. To visualize it, the photo story theory is used as the basis for creation by applying a narrative photo story to the pig hunting activities of the people of Patamuan District. Photo stories are believed to be able to retell the reality seen by the eye which will be conveyed to the general public, so that besides adding insight this final project can become an archive and be useful at present and in the future.